Advances in Ionic Thermoelectrics: From Materials to Devices. Issue 9 (20th January 2023) - Sun, Shuai; Li, Meng; Shi, Xiao‐Lei; Chen, Zhi‐Gang
Abstract: As an extended member of the thermoelectric family, ionic thermoelectrics (i‐TEs) exhibit exceptional Seebeck coefficients and applicable power factors, and as a result have triggered intensive interest as a promising energy conversion technique to harvest and exploit low‐grade waste heat (<130 °C). The last decade has witnessed great progress in i‐TE materials and devices; however, there are ongoing disputes about the inherent fundamentals and working mechanisms of i‐TEs, and a comprehensive overview of this field is required urgently. In this review, the prominent i‐TE effects, which set the ground for i‐TE materials, or more precisely, thermo‐electrochemical systems, are first elaborated. Then, TE performance, capacitance capability, and mechanical properties of such system‐based i‐TE materials, followed by a critical discussion on how to manipulate these factors toward a higher figure‐of‐merit, are examined. After that, the prevalent molding methods for assembling i‐TE materials into applicable devices are summarized. To conclude, several evaluation criteria for i‐TE devices are proposed to quantitatively illustrate the promise of practical applications. It is therefore clarified that, if the recent trend of developing i‐TEs can continue, the waste heat recycling landscape will be significantly altered. Abstract : In this review, the progress in ionic thermoelectrics, including fundamental theories, material designations, property characteristics, performance regulations, molding methodologies, and device employments, are comprehensively summarized. Perspective remarks on the outlook and challenges of ionic thermoelectrics are also discussed.